Antioxidant and radical scavenging activities of Asphodelus aestivus Brot. extracts - Peksel, Aysegul; Imamoglu, Sema; Kiymaz, Nilay Altas; Orhan, Nurdagul (TAYLOR & FRANCIS INC, 2013)
Asphodelus aestivus Brot. is a common spring-flowering geophyte encountered on the Marmara, Aegean, and Mediterrenean coasts of Turkey, which has been utilized traditionally for culinary and medicinal purposes. In the present study, different antioxidant tests were employed in order to evaluate the antioxidant activities of methanolic and acetone extracts of A. aestivus Brot. leaves. In addition, the results were compared with natural and synthetic antioxidants. The levels of total flavonoid, total chlorophyll, and total carotenoid contents of the extracts were also determined. Both extracts showed good total flavonoid content, inhibited lipid peroxidation, and showed radical scavenging activities.
Keywords: Asphodelus aestivus Brot; Antioxidant activity; Free radical; Scavenging activity; Superoxide anion radical; MEDICINAL-PLANTS; RAMOSUS TUBERS; ANTHRAQUINONES; POLYPHENOLS; MICROCARPUS; GLYCOSIDES; LEAVES; Food Science & Technology